2015
DOI: 10.4172/2329-888x.1000117
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of Solute Carrier (SLC2A) Genes in Milk Derived Mammary Epithelial Cells during Different Stages of Lactation in Sahiwal (Bos indicus) Cows

Abstract: Solute carriers (SLC2A/ GLUT) are one of the major types of transporter superfamily that have been predominantly involved in active transport of glucose across the plasma membrane. Glucose uptake by mammary epithelial cells (MECs) is an important step in the milk synthesis during lactation, and hence directly influences the milk yield. Use of MEC isolated from milk has been speculated to be a good alternative to mammary gland tissues in order to understand the expression profile of important genes associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…SLC4A4 is a solute transporter, belonging to one of the major transporter superfamilies mostly involved in the active transport of glucose. Glucose uptake by mammary epithelial cells is a crucial stage in milk synthesis, and therefore, directly influences MILK [76]. Furthermore, NIM1K and ZNF131 have been reported to prolong lactation period culminating in higher milk production levels in Canadian dairy cattle [36].…”
Section: Candidate Genes For Milk Yieldmentioning
confidence: 99%
“…SLC4A4 is a solute transporter, belonging to one of the major transporter superfamilies mostly involved in the active transport of glucose. Glucose uptake by mammary epithelial cells is a crucial stage in milk synthesis, and therefore, directly influences MILK [76]. Furthermore, NIM1K and ZNF131 have been reported to prolong lactation period culminating in higher milk production levels in Canadian dairy cattle [36].…”
Section: Candidate Genes For Milk Yieldmentioning
confidence: 99%
“…However, Mann et al [ 50 ] reported the same level of GLUT1 expression in both stages of lactation (early, peak). On the other hand, Pradeep et al [ 51 ] showed that GLUT1 gene expression was highest during the cows' peak lactation stage and lowest during the cows' early lactation stage. Compared to buffalo, GLUT1 gene expression was found to be higher in cows, as reported by both Yadav et al [ 30 ] and Pradeep et al [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Pradeep et al [ 51 ] showed that GLUT1 gene expression was highest during the cows' peak lactation stage and lowest during the cows' early lactation stage. Compared to buffalo, GLUT1 gene expression was found to be higher in cows, as reported by both Yadav et al [ 30 ] and Pradeep et al [ 51 ]. Since the quantity of milk produced is directly proportional to the amount of glucose absorbed by the alveolar epithelial cells of the mammary gland Pradeep et al [ 51 ], and since GLUT1 is the predominant glucose transporter that is responsible for glucose transmission in the mammary gland, the GLUT1 expression would be correlated with milk production throughout the two stages of lactation.…”
Section: Discussionmentioning
confidence: 99%